Considerations of the scale of radiocarbon offsets in the east mediterranean, and considering a case for the latest (most recent) likely date for the Santorini eruption - Manning, Sturt W.; Kromer, Bernd (Radiocarbon, 2012)
The debate over the dating of the Santorini (Thera) volcanic eruption has seen sustained efforts to criticize or challenge the radiocarbon dating of this time horizon. We consider some of the relevant areas of possible movement in the 14C dating—and, in particular, any plausible mechanisms to support as late (most recent) a date as possible. First, we report and analyze data investigating the scale of apparent possible 14C offsets (growing season related) in the Aegean-Anatolia-east Mediterranean region (excluding the southern Levant and especially pre-modern, pre-dam Egypt, which is a distinct case), and find no evidence for more than very small possible offsets from several cases. This topic is thus not an explanation for current differences in dating in the Aegean and at best provides only a few years of latitude. Second, we consider some aspects of the accuracy and precision of 14C dating with respect to the Santorini case. While the existing data appear robust, we nonetheless speculate that examination of the frequency distribution of the 14C data on short-lived samples from the volcanic destruction level at Akrotiri on Santorini (Thera) may indicate that the average value of the overall data sets is not necessarily the most appropriate 14C age to use for dating this time horizon. We note the recent paper of Soter (2011), which suggests that in such a volcanic context some (small) age increment may be possible from diffuse CO2 emissions (the effect is hypothetical at this stage and has not been observed in the field), and that “if short-lived samples from the same stratigraphic horizon yield a wide range of 14C ages, the lower values may be the least altered by old CO2.” In this context, it might be argued that a substantive “low” grouping of 14C ages observable within the overall 14C data sets on short-lived samples from the Thera volcanic destruction level centered about 3326-3328 BP is perhaps more representative of the contemporary atmospheric 14C age (without any volcanic CO2 contamination). This is a subjective argument (since, in statistical terms, the existing studies using the weighted average remain valid) that looks to support as late a date as reasonable from the 14C data. The impact of employing this revised 14C age is discussed. In general, a late 17th century BC date range is found (to remain) to be most likely even if such a late-dating strategy is followed—a late 17th century BC date range is thus a robust finding from the 14C evidence even allowing for various possible variation factors. However, the possibility of a mid-16th century BC date (within ~1593-1530 cal BC) is increased when compared against previous analyses if the Santorini data are considered in isolation. DOI: 10.2458/azu_js_rc.v54i3-4.16169
Gesehen am 18.09.2018